Spatial Variability of Selected Chemical Characteristics of Paddy Soils in Sawah Sempadan, Selangor, Malaysia - A. W., Aishah; Darus, Siti Zauyah; Abd Rahim, Anuar; Ishak, Che Fauziah (Malaysian Society of Soil Science, 2010)
A study was conducted to evaluate the spatial variability of selected soil chemical properties of paddy soils in the Barat Laut Paddy Project area in Selangor. A total of 138 geo-referenced soil samples were collected from the area at 0-20 cm depth after harvest, at an interval of 80-90 m to determine the selected chemical properties: pH, organic carbon, total nitrogen (N), available phosphorus (P) and exchangeable potassium (K). Geostatistical analyses were applied to examine the within-field spatial variability using semivariograms and kriged maps. Kriged maps for each property were prepared using geostatistical software package based on the results of spatial dependence. The effective ranges for the areas were about 6 km for pH, 1 km for organic carbon, 8 km for total N and available P and 9 km for exchangeable K, respectively. Kriged maps produced showed that most of the area have pH values within the range of 4-4.5 (moderately acidic) and high amount of organic carbon content (3-5%). The kriged maps also showed that a large portion of the study area (66%) have high total N (0.30-0.40%), with low amount of available P (< 40 mg kg-1) covering 70% of the total study area, while most of the area have optimum content of exchangeable K (> 0.10 cmol(+) kg-1). These results suggest the need for a site specific approach in managing paddy soils particularly with regard to nutrient management. The results also suggested that future soil sampling in these area can be carried out by increasing the sampling interval depending on the soil properties, and appropriate management should be applied according to the variations which exist.